Evaluasi Sistem ATR/BPN Berbasis Webuse dan Heuristic Evaluation - Sapni Danil; Muhammad Said Hasibuan (Journal of Digital Literacy and Volunteering, 2024)
The Ministry of Agrarian Spatial Planning/National Land Agency (ATR/BPN) provides services that aim to facilitate the public in managing the legality of land services online, which can be accessed anywhere with the aim of providing convenience and security to the public in conducting service transactions as an effort to increase the ease of doing business, but the benefits of this website have not been measured for the usability of the website effectively and efficiently. Therefore, this research was conducted with the aim of evaluating and assessing the appearance of the interface with the Heuristic Evaluation method and the Web Usability Evaluation Tool (WEBUSE) and measuring display development. ATR/BPN website to help the community. The research method uses the Web Usability Evaluation Tool (WEBUSE) in the form of a questionnaire and then evaluates it using Heuristic Evaluation. The research that has been carried out has produced findings that show the ATR/BPN Website has a level that is good enough to be used by Notary/PPAT employees and the community. From the usability test, it shows that the quality attribute can be said to be of high value. The conclusion of the study shows that each category of WEBUSE Evaluation has a usability value of 0.69 points, which indicates the usability level is at a good level while the lowest value is in the visibility of system status (feedback) variable (H1 of 61.02%) according to the usability level at the Moderate. This means it's not working properly. And the Savery Rating is 1.3119 when rounded up to 1 category of cosmetic problem that takes time to fix.